Migración del sistema de red (IPv4) al protocolo (IPv6) con implementación de (IPSEC) en la plataforma Windows para la seguridad del protocolo dentro del GAD Municipal del Cantón Pujilí ubicado en el barrio centro y perteneciente a la Provincia de Cotopaxi en el periodo 2012-2013 - Rodríguez, Luis Miguel (2013)
Due to the growth the Internet use, the advancement of technology, the development of telecommunications and the increasing demand from companies there has been a shortage of IPv4 addresses. Preventing this situation, the IETF has developed the new IPv6 protocol, as an evolutionary step from IPv4 to solve the shortage of IP addresses and strengthen the development of networks, Internet and technology. Takinng into consideration this new protocol this research work aims to migrate the IPV4 to IPV6 protocol network with IPSEC implementation on the Windows platform at GAD Municipal del canton Pujilí. Before the migration, a process of analysis in terms of hardware and software within the entire network was done. It permitted better choices and considerations when implementing the new protocol. Similarly surveys and interviews were applied for both administrators and users of the network in order to know the current state of it in order to establish the viability and development of the thesis project. Besides using analytical methods such as synthetic, inductive-deductive, hypothetical-deductive, it was possible to obtain knowledge, investigate and determine solutions in relation to this issue defined in this study. The results have showed that the network works without drawbacks and computer securities are priority for the institution staft, but it is important to take into account some changes in hardware and software network during the migration to IPV6 with IPSEC. Finally this thesis will contribute to the improvement of the network in terms of stability, flexibility and simplicity also including securities within the protocol in order to facilitate the authentication, integrity and confidentiality of communications with faster and more reliable data.